2010
DOI: 10.1038/jhh.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Non-synonymous single-nucleotide polymorphisms associated with blood pressure and hypertension

Abstract: In this study, we determined the association of 1180 non-synonymous single-nucleotide polymorphisms (SNPs) with systolic blood pressure (SBP) and hypertensive status. A total of 8842 subjects were taken from two community-based cohorts-Ansung (n ¼ 4183) and Ansan (n ¼ 4659), South Korea-which had been established for genome-wide association studies (GWAS). Five SNPs (rs16835244, rs2286672, rs6265, rs17237198 and rs7312017) were significantly associated (P-values: 0.003-0.0001, not corrected for genome-wide sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…This study also demonstrates that our approach of using functional SNPs, such as regulatory SNPs (TFBS-SNPs) in addition to a previous GWAS on nonsynonymous SNPs, 9 identifies the genetic variations that biologically linked to blood pressure regulation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This study also demonstrates that our approach of using functional SNPs, such as regulatory SNPs (TFBS-SNPs) in addition to a previous GWAS on nonsynonymous SNPs, 9 identifies the genetic variations that biologically linked to blood pressure regulation.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, we employed an alternative approach, using nonsynonymous single-nucleotide polymorphisms (SNPs) in the GWAS data, and identified more SNPs located in arginine decarboxylase, phospholipase D1, brain-derived nuclear factor and an unknown gene (AC089987). 9 Although these nonsynonymous SNPs did not have strong P-values (1.0Â10 -3 oPo4.8Â10 -2 ), they appeared to be biologically linked to blood pressure. 9 This limited success encouraged us to examine other regulatory SNPs that were obtained in the GWAS data of Korean Association REsource, generated by Affymetrix 5.0 SNP array (Affymetrix, Inc., Santa Clara, CA, USA), to identify additional genetic factors that regulate blood pressure.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The etiology of hypertension is multi-factorial and includes genetic and environmental components. PLD elevation has been reported in vascular smooth muscle cells from spontaneously hypertensive rats (SHR; an animal model of hypertension) (Kondo et al, 1994;Freeman et al, 1995), and recently, genome-wide association studies (GWASs) showed that PLD2 is mutated (Arg172 to Cys) in patients with a hypertensive status (Hong et al, 2010). Although further studies on the interrelationship between PLD2 and hypertension are required, these GWASs demonstrated the biological relevance of PLD2 in the pathophysiology of hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…rs13002573 and rs1446468 lay in the FIGN locus, both of which were significantly associated with blood pressure and hypertension in the Asian study, 7 suggesting that the FIGN locus regulates blood pressure in humans and is a major risk factor of hypertension. The FIGN encoded a member of ATPases associated with the diverse cellular activities (AAA proteins) group.…”
mentioning
confidence: 95%